DESIGN AND IMPLIMENTATION OF WEB BASED AUGMENTED REALITY APPLIED ON FSA APPLICATION - IKA (NIM : 23208329); PEMBIMBING : Dr. Ir. Hilwadi Hindarsah, M.Sc,; Ir Tunggal Mardiono, M.S, AGUNG
Interaction in a Fashion Shopping Assistance (FSA) application is a close representation of reality about the actual activities carried out in a fitting fashion, which is commonly practiced in fitting room at a fashion store. To better provide a real effect then the FSA application is built by implementing the Augmented Reality technology. Augmented Reality (AR) is an environment that includes 3D virtual objects into the real environment in real-time. This research will include AR technology into online fashion sales application so this applications become more alive with the object of 3D fashion. AR applications require a streaming video taken from camera as a source of input, then this application will track and detect the marker by using the tracking system, after the marker is detected, the 3D clothing model drawn on the marker as if the real fashion model. Tests carried out using three different markers of his size, to find out the nearest and farthest distance the appearance of 3D objects. Testing is also done with a different webcam, to see if the application is running well when using a different webcam. Evaluation of preliminary design applications which are built based on augmented reality are conducted by distributing questionnaires to the respondents. Based on test results directly in the trial by the respondents, the majority of respondents assess the application of this model is more attractive, interactive, and have more experience, when compared with other models of visual aids.